The Preparation and Implementation of School Improvement Plans (SIPs): Its Implication in Improving Learning Outcomes - Budhathoki, Shak Bahadur (Molung Educational Frontier, 2023)
In the last two decades, Nepal’s community (public) schools have been preparing, Implementing and reviewing School Improvement Plans (SIPs) periodically. Schools submit SIPs to the Local Government (LG) to get disbursed school funds annually. One of the components of SIP includes learning outcomes (MoE, 2017).In this context, there is a general lack of research on the process of making Sips and its effects on learning outcomes. To fill the existing lack of knowledge in this field, this research aims to answer two interrelated questions. First, what is the policy process of preparing SIP and how it is practiced? Second, what are the effects of teaching and learning process as envisioned in the SIPs on students ‘learning outcomes? This research applies qualitative methods, analysing content of selected Sips of three community schools of Kailali district from the far western region, especially focusing on the plans to improve learning outcomes. Building on these findings, case studies are conducted in the schools using semi – structured interviews by taking into consideration experiences of teachers, students, parents, SMC/PTA Chairs and members, resource persons and LG authorities (ten interviews in total) in July 2019, exploring how SIP has been understood and realized in practice on the ground. It is generally observed that the process of preparing and implementing SIPs has positive correlation with learning outcomes even if it is minimal over the time. In fact, the will – power on the part of school stakeholders is the key for the quality SIP, and the policy as envisioned at the centre has partially been implemented at grassroots.